Wallpaper = Tapeten = Papiers peints - Fischer, Joachim (Architecture compact, 2008)
"After an amazing abundance of colours and form in the 1960s, high-quality wall covers were increasingly substituted by the ubiquitous woodchip paper. In the meantime, though, wallpaper has evolved into one of the trend topics in materials. Traditional manufacturers are now employing renowned designers to create new patterns which are clearly inspired by current trends or even evolve into trend setters of their own right. This book explores wallpaper designs by individual designers and studios around the world. Patterns and textures are brought to life through a vast array of full-colour illustrations throughout."--Publisher description